Aspek Hukum Peran TNI Mengatasi Serangan Siber dalam Rangka Pertahanan Keamanan Nasional - Fauziah Nauri Qisty; Bayu Setiawan; Anang Puji Utama (Wajah Hukum, 2025)
Cyberattacks are a growing and increasingly threatening form of non-traditional threat that endangers national security stability in the digital age. In this context, cybersecurity has become an integral part of the nation's defense system, making the role of the Indonesian National Army (TNI) in facing cyberattacks increasingly relevant and urgent. However, the legal aspects governing the authority of the Indonesian National Armed Forces (TNI) in the cyber domain still raise debate, particularly due to the lack of comprehensive and specific regulations. This research aims to examine and understand the legal basis governing the role of the Indonesian National Armed Forces (TNI) in addressing cyber threats, analyze the limits of its legal authority within the context of national cyber defense, and evaluate the implementation of existing policies. This research uses a normative juridical method, as well as relevant legislation (statute approach) and conceptual (conceptual approach) approaches. The research results indicate that although the role of the Indonesian National Armed Forces (TNI) is highly strategic in facing covert and high-risk cyber threats to national sovereignty, the involvement of the TNI must be based on a clear and firm legal framework, carried out through effective coordination with relevant institutions, and always uphold applicable legal principles.